Early onset of diffuse melanosis cutis under pembrolizumab therapy illustrates the limitations of anti-PD-1 checkpoint inhibitors. Issue 5 (October 2018) - Thiem, Alexander; Schummer, Patrick; Ueberschaar, Simon; Kerstan, Andreas; Kneitz, Hermann; Schrama, David; Appenzeller, Silke; Meierjohann, Svenja; Schilling, Bastian; Goebeler, Matthias; Gesierich, Anja
Abstract : Anti-PD-1 targeted immunotherapies have revolutionized the treatment of advanced melanoma and other tumor entities, and long disease-free intervals have been reported in responding patients. However, a considerable number of patients still progress rapidly after the start of anti-PD-1 antibodies. Here, we document two patients, 78 and 85-year old, who suffered from advanced BRAF-V600 wild-type melanoma and received pembrolizumab 2 mg/kg every 3 weeks as the first systemic treatment. After only one, respectively, two infusions of pembrolizumab, both patients developed melanuria and diffuse melanosis cutis (DMC) on sun-exposed areas of their skin. Both also had liver metastases, which have been reported to be associated with DMC before. Pembrolizumab was stopped because of rapid tumor progression and both patients died within 2 months after manifestation of DMC. We conclude that DMC is a condition that may be a negative predictor of response to anti-PD-1 treatment. With respect to the very short survival, which is even shorter than that reported after conventional therapies, it needs to be evaluated whether immunotherapy may be a (relative) contraindication in DMC patients when another treatment option, that is targeted therapy, is available.